Glasba in glasbeno življenje na Slovenskem v 17. stoletju - Kokole, Metoda (De musica disserenda, 2010)
The main goal of this article is to present the state of research on music and musical life in Slovenia during the seventeenth century. The topics that have been in the past covered in some detail include early seventeenth-century music prints and manuscripts from the time of Prince-Bishop of Ljubljana Tomaž Hren; the composers Isaac Posch, Gabriello Puliti, and Janez Krstnik Dolar; the musicalia of the cathedral in Koper; and the Academia Philharmonicorum Labacensium. However, at present, knowledge on music in important centers of peripheral areas such as Maribor and Ptuj is scant; musical activities within monastic and other religious centers are under-researched; and music education in this period represents a complete lacuna.
Keywords: glasba; music; 17.st.; Slovenia; Slovenija; raziskave; history; zgodovina